The Effect Of Transformational Leadership And Perceived Organisational Support On Work-Life Balance - Muthia Roza Linda (Universitas Negeri Padang, 2017)
Purpose of these study are analyzing the influence of transformational leadership and perceived organisational support to work-life balance on banking employees in Padang. Respondents are 94 female employee at banks, survey was conducted as the sampling technique because Work-Life Balance is a social phenomenon that could be captured and generalized better by using a survey method. To answer the purposes of these study, the data were analyzed by using multiple linear regression using SPSS ver.16. The results revealed that transformational leadership has a positive and significant effect on the Work-Life Balance. The magnitude of the effect of transformational leadership and perceived organisational support, to the work-life balance is 49.8%.